Practicing convict criminology: lessons learned from British academic activism - Aresti, Andreas (Critical criminology, 2016)
Joanne Belknap’s recent ASC presidential address included a critique of Convict Criminology’s activism. A number of concerns were provided, although of particular importance here are, first, Belknap’s concerns regarding the absence of ‘marginalized voices’ in the Convict Criminology network. Second, the issue of defining how non-con academics function as Convict Criminology group members. This paper responds to these criticisms. Specifically, we discuss the question of ‘representation’ in BCC and our attempts to remedy this issue. We also draw attention to the academic activism that British Convict Criminology is conducting in Europe. This includes a detailed discussion of the collaborative research-activist activities that involve non-con as well as ex-con academic network members. We demonstrate how these collaborations explain the vital group membership role that non-con academics assume in the activism of Convict Criminology.